2013
DOI: 10.1186/1471-2466-13-15
|View full text |Cite
|
Sign up to set email alerts
|

The association between asthma control, health care costs, and quality of life in France and Spain

Abstract: BackgroundCurrent asthma management guidelines are based on the level of asthma control. The impact of asthma control on health care resources and quality of life (QoL) is insufficiently studied. EUCOAST study was designed to describe costs and QoL in adult patients according to level of asthma control in France and Spain.MethodsAn observational cost of illness study was conducted simultaneously in both countries among patients age greater or equal to 18 with a diagnosis of asthma for at least 12 months. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
88
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 22 publications
(19 reference statements)
8
88
4
3
Order By: Relevance
“…In Spain, the average cost (euros/3 months/patient) of controlled asthma was €152.60, increasing steadily to €241.20 and €556.80 in partly controlled and uncontrolled patients. Asthma medication was the main driver of the direct costs for controlled and partly controlled disease, whereas costs associated with hospitalizations for asthma and emergency room visits were higher in uncontrolled asthma patients [30]. In the present study, the cost-effectiveness analysis showed that adding FeNO testing to standard guideline care resulted in savings of €62.53 per patient-year compared with standard guideline-directed care alone (Table 3).…”
Section: Discussionmentioning
confidence: 65%
“…In Spain, the average cost (euros/3 months/patient) of controlled asthma was €152.60, increasing steadily to €241.20 and €556.80 in partly controlled and uncontrolled patients. Asthma medication was the main driver of the direct costs for controlled and partly controlled disease, whereas costs associated with hospitalizations for asthma and emergency room visits were higher in uncontrolled asthma patients [30]. In the present study, the cost-effectiveness analysis showed that adding FeNO testing to standard guideline care resulted in savings of €62.53 per patient-year compared with standard guideline-directed care alone (Table 3).…”
Section: Discussionmentioning
confidence: 65%
“…350 million patients worldwide (Aldubi et al, 2015;Bahadori et al, 2009;Busaidi-Al et al, 2013;D'Amato et al, 2015;Litonjua and Weiss, 2007). Prevalence of this disease is steadily increasing, particularly in industrial countries and in some European countries is already higher than 10% of infantile population (Litonjua and Weiss, 2007;Bedouch et al, 2012;Doz et al, 2013;Kasak, 2005;Negro et al, 2007). This trend is very similar in the Czech Republic, particularly in the infantile population (Kasak, 2005;Petru, 2008;Pohunek and Slamova, 2009;Pohunek et al, 2009).…”
Section: Introductionmentioning
confidence: 64%
“…Problems in evidence of AB, leading to disproportional evidence of AB in individual regions, are also significant (Gudelj et al, 2012;Hansen et al, 2012). An exact and early diagnosis can significantly reduce progression of clinical manifestation of AB and thus strongly lower financial burden (Bahadori et al, 2009;Litonjua and Weiss, 2007;Edwards et al, 2011;Doz et al, 2013;Pohunek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors could affect QoL of people with asthma, such as age, socioeconomic status, education level and marital status. These factors could modify classification, diagnosis and treatment of asthma (14). Despite the importance of assessing QoL in chronic respiratory diseases such as asthma, there has been limited research on QoL in people with asthma in the Islamic Republic of Iran.…”
Section: Introductionmentioning
confidence: 99%